The Existence of The Fiqh Madhhab of Thought in Islamic Boarding Schools: A Case Study at Darussalam Islamic Boarding School Gontor 11 Poso, Central Sulawesi - Abd. Raziq, Irsyad; Syahrul Ramadhan; Putri Marissa (Universitas Islam Negeri Alauddin Makassar, 2022)
The Fiqh School of Thought is one alternative to exercising the Shari’a in Pondok Modern Gontor, and students are not required to adhere to a particular ideology. It was asserted that an Islamic boarding school could not be gray but should be oriented to one school of thought. Therefore, this study aimed to determine the roles and existence of a school of thought in addressing diversity with a sociological approach in Modern Islamic Boarding School Gontor 11 Poso Central Sulawesi. Based on the results, no particular school of thought became a reference and allowed student adherence to one of the qualified schools, according to Ahlu Sunnah. In the transformation of the role, the scholars (ulama) were used as the leading figure with an adopted school of thought. However, they did not force the will on their students to follow the adopted school of thought. Kyai (Islamic instructor) is also necessary to explain that most al-Shafi’i names are found in Indonesia, which urges students to study and appreciate the Al-Sya’ir school of thought. Therefore, it may be warmly appreciated and not conflict with the community.